The Impact of Feminist Discourse on Disney Animation: (From Stereotypical Portrayal into Empowered Females) - Reham AlBassam; Dr. Anoud Alhamad (Journal of Arts, Literature, Humanities and Social Sciences, 2025)
Walt Disney has produced numerous masterpieces and animated films since 1923, being one of the leading entertainment industries. With the unforgettable choices of topics, themes and diverse portrayal of characters, this paper overviews the evolution of Disney portrayal of human female protagonists across selected films. A qualitative descriptive analysis interprets female protagonists in eight animated films depicted in the Classics, Renaissance, and the New Age eras. These include Snow White and the Seven Dwarfs (1937), Cinderella (1950), Pocahontas (1995), Mulan (1998), Brave (2012), Frozen (2013-2019), Raya and the Last Dragon (2021), and Moana (2016-2024). This chronological overview focuses on the gendered behavior and stereotypical portrayal of female protagonists within the context of Eurocentric beauty standards. It traces the evolution of these portrayals through a theoretical framework of stereotypes as influenced by various waves of feminism, thereby enabling a nuanced investigation of the development of these characters from traditional princesses to empowered female protagonists.